Analisis Sudut Pisau Pada Mesin Pencacah Rumput Gajah Untuk Pembuatan Silase Pakan Ternak Sapi - Nugraha, Muhammad Erlangga Adi; Wulandari, Diah; Utama, Firman Yasa; Nugroho, Aji (CV. SINAR HOWUHOWU, 2026)
This study examines how the blade angle of an elephant grass chopping machine affects the chopping results used for making cattle feed silage. Elephant grass needs to be chopped to a standard size for silage production, with the ideal chop length ranging from 2–5 cm and relatively uniform, so that the fermentation process runs properly and the feed is easier for livestock to consume. The research was conducted using an experimental method with 1 kg of fresh elephant grass for each trial. The chopped output was classified into three size categories: <2 cm, 2–5 cm, and >5 cm, to determine which met the silage standard most effectively. The study tested three blade angles—30°, 45°, and 60°—and three machine rotational speeds (1700 rpm, 2000 rpm, and 2300 rpm) to evaluate their effects on chopping time, cut size distribution, and processing capacity. The results show that the best performance in terms of machine rotational speed at the 30° blade angle occurred at 2300 rpm. The highest percentage of chopped material within the 2–5 cm size range was obtained at a 45° blade angle, reaching approximately 55–58% of the total chopped output, indicating the most optimal conformity with silage size standards.